Bodies at play: the role of intercorporeality and bodily affordances in coordinating social play in chimpanzees in the wild - van Boekholt, Bas; Wilkinson, Ray; Pika, Simone (Frontiers in Psychology, 2024)
The comparative approach is a crucial method to gain a better understanding in the behaviour of living humans and other species. Additionally, it is central in disentangling the puzzle of language evolution.Traditionally, studies have predominantly focused on intentionally produced signals in communicative interactions. However, in collaborative and highly dynamic interactions such as play, underlying intentionality is difficult to assess and often interactions are negotiated via body movements rather than signals. This "lack" of signals has led to these dynamic contexts being widely ignored.The aim of this paper is threefold. First, we will show how comparative research into communication can benefit from taking the intentionality-agnostic standpoint used in conversation analysis. Second, we will introduce the concepts of 'intercorporeality' and 'bodily affordance' and show how they can be applied to the analysis of communicative interactions of nonhuman animals. Third, we will use these concepts to investigate how chimpanzees (Pan troglodytes schweinfurthii), initiate, end and maintain contact social play. Our results showed that bodily affordances are able to capture elements of interactions that more traditional approaches fail to describe. Both participants make use of bodily affordances to achieve coordinated engagement in contact social play. Additionally, these interactions can display a sequential organization by which one 'move' by a chimpanzee is responded to with an aligning 'move', which allows for the co-construction of the activity underway. Hence, the present approach innovates on three fronts: First, it allows for the analysis of interactions that are often ignored because they do not fulfil criteria of intentionality and/or consist of purely body movements. Second, adopting concepts from research on human interaction enables a better comparison of communicative interactions in animal species without a too narrow focus on intentional signalling only. Third, adopting a stance from interaction research that highlights how practical action can also be communicative, we highlight ways in which chimpanzees can communicate through their embodied actions as well as through signalling. With this first step, we hope to inspire new research into dynamic day-to-day interactions involving both "traditional" signals and embodied actions, which, in turn, can provide insights into evolutionary precursors of human language.